Comparison of two construction algorithms for Takagi-Sugeno fuzzy models - Nelles, Oliver; Fink, Alexander; Babuška, Robert; Setnes, Magne (Zielona Góra: Uniwersytet Zielonogórski)
This paper compares two different approaches to the construction of Takagi-Sugeno fuzzy models from data. These models approximate nonlinear systems by means of interpolation between local linear models. The main issue in the construction of Takagi-Sugeno models is the decomposition of the operating space into validity regions for the local models.
Keywords: modeling; identification; Takagi-Sugeno fuzzy models; local linear models; turbocharger